Pollen Characteristics of Some Species in the Genus Bacopa - Paopun, Yupadee (Microscopy and Microanalysis Research – The Journal of The Microscopy Society of Thailand, 2018)
Plants in the genus Bacopa are important herbs, which makes them suitable to be studied about pollen morphology because it can be used to identify medicinal plants. Pollens of two Bacopa species were examined under light and scanning electron microscopes. The two species were similar in their aperture type, shape, and exine sculpturing. The aperture type of both species is compound aperture and tricolporate. The shapes of polar view are circular and semi-angular. The shapes of equatorial view are spheroidal, oblate-spheroidal and prolate-spheroidal. On the other hand, the species differed in their number of lumina. The exine sculpturing appears to have several lumina. It was found that the number of lumina on the exine sculpturing of B. monnieri was larger than on B. caroliniana. As a result, the morphological characteristics of the pollen can be used for species identification of this genus.